Selecting processes for automation - Farinha, Diogo Miguel da Silva (2021)
With the increasing demand for digitalization, organizations are looking to take advantage of the emerging technologies such as Robotic Process Automation to increase the performance of their business, which makes it essential to identify and select the best cases to automate in order that the compensation of those projects can be beneficial to the organizations. However, initiating this transition can be difficult without a clear path that the stakeholders need when it comes to selecting the processes that are suitable for automation. Therefore, the objective of this study is to identify a set of criterions to identify the best-suited processes to automate. To achieve the objective of this research, a Delphi study will be performed so that RPA professionals can evaluate and tune specific criteria to be used to choose business processes to be automated. According to the Systematic Literature Review performed for this study, only one article presents a 3-step model to select suited business processes for automation. Therefore, this research aims to identify the main criteria evaluated by automation experts to rank business processes suitable for automation. In this study was possible to collect multiple criterions ranked by RPA experts, which were later used to evaluate business processes in multiple organizations. The results of the evaluation compared the order of development followed by the organization and the order suggested by the were the order of development followed by the organizations matched five times out of six with the order of the evaluation by criteria collected in this study.